PERSPEKTIF MASLAHAH MURSALAH TERHADAP PERNIKAHAN DI BAWAH TANGAN (Studi Kasus di Desa Gedang kulut Kecamatan Cerme Kabupaten Gresik) - Linda Safitri; Abdullah Afif (JOURNAL SAINS STUDENT RESEARCH, 2024)
This thesis is the result of the author's research entitled "Marriage Under the Hands of Maslahah Murlah's Perspective (Case Study of Gedang Kulut Village, Cerme District, Gresik Regency)". This research aims to answer the question in the problem formulation, namely: What are the causes and impacts that influence the occurrence of underhanded marriages in Gedang Kulut village? What is the perspective of maslahah murlah and the views of the people of Gedang Kulut village regarding underhanded marriage. The type of research used in this thesis research is qualitative with an empirical normative approach method. The data collection method is by using interview, observation and documentation techniques. The results of this research show that the factors behind marriage under the hand are the administrative limitations of parents and the factor of promiscuity. Meanwhile, the impact of underhanded marriage is economic, health and psychological.